Investigating the relationship between perceived school kindness and academic engagement: Mediating role of academic hope in high school students - Hasan Moradi; Ali Akbar Shikhi Fini; Abdolvahab Samavi (University of Hormozgan, 2022)
This study examined the relationship between perceived school kindness, academic hope, and academic engagement among a sample of students. Structural equation modeling was used to analyze the data, and the results indicated that perceived school kindness was significantly and positively associated with academic engagement and academic hope. Academic hope was also significantly and positively associated with academic engagement. Furthermore, academic hope partially mediated the relationship between perceived school kindness and academic engagement. These findings suggest that students who perceive their school as kind are more likely to feel engaged in their academic work and have hope for their academic future. The results of this study have important implications for educators and policymakers who seek to promote positive outcomes among students. Future research could investigate effective interventions that promote both hope and engagement and examine the mechanisms through which these constructs influence each other.